Financial Flows Management Based on the Analysis of Their Interaction - Vasiurenko, O.; Lyashenko, V.; Hushynets, D. (IJAMSR, 2022)
Economic dynamics is one of the central aspects of analysis in various studies. This is due both to the analysis of the functioning of individual business entities, and the development of the economy as a whole. No less important is the analysis of effective management, which, ultimately, determines the level of functioning and development of various business entities. The activity of any business entity has an impact on the sustainable development of both individual industries or areas of the economy, and other business entities. Therefore, various management issues are constantly in the spotlight. Among such issues, special attention is paid to the movement of financial flows. Financial flows reflect different areas of activity of a business entity, the corresponding movement of its tangible and intangible resources, changes in the dynamics of the volume of financial resources.Then we can talk about a variety of financial flow that reflects different aspects of the activity of a business entity. Moreover, each financial flow is a time series that allows you to conduct research for different time intervals. Consequently, the management of a business entity can be viewed through the management of the relevant financial flows. It is important to know the interaction of such flows, their relationship in time. For this analysis, we use the wavelet methodology. One of the methods for analyzing the relationship between various financial flows can be wavelet coherence. This approach makes it possible to evaluate the mutual dynamics of financial flows. At the same time, such an analysis can be done for different time horizons from the time interval that is be ing studied. As a result, we conclude about the effectiveness of the corresponding level of management. This allows you to make the necessary adjustments and improve the overall management system of a business entity. Using specific examples, we consider wavelet coherence estimates that reflect the mutual movement of various financial flows. Such an analysis is carried out for different time horizons. This allows you to specify the result of management, its effectiveness. The paper presents various drawings, graphs and diagrams that help to understand the logic of the study.
Keywords: management; wavelet coherence